Rapid Determination of the Specificity Constant of Irreversible Inhibitors (kinact/KI) by Means of an Endpoint Competition Assay. (1st October 2015) - Miyahisa, Ikuo; Sameshima, Tomoya; Hixon, Mark S.
Abstract: Owing to their covalent target occupancy, irreversible inhibitors require low exposures and offer long duration, and their use thus represents a powerful strategy for achieving pharmacological efficacy. Importantly, the potency metric of irreversible inhibitors is k inact / K I not IC50 . A simple approach to measuring k inact / K I was developed that makes use of an irreversible probe for competitive assays run to completion against test compounds. In this system, the k inact / K I value of the test compound is equal to ( k inact / K I )probe ×[probe]/IC50 . The advantages of this method include simplicity, high throughput, and application to all target classes, and it only requires an in‐depth kinetic evaluation of the probe. Abstract : Das Maß der Wirksamkeit von irreversiblen Inhibitoren ist das Verhältnis k inact / K I und nicht IC50 . Ein einfacher Ansatz zur Messung von k inact / K I nutzt eine irreversible Sonde für Konkurrenzassays gegen Testverbindungen. In diesem System ist k inakt / K I der Testverbindung gleich ( k inakt / K I )Sonde ×[Sonde]/IC50 . Weitere Vorteile des Verfahrens sind hoher Durchsatz, Anwendbarkeit auf alle Zielklassen und eine rein kinetische Auswertung.